Decision-Making Under Risk in Children, Adolescents, and Young Adults - Paulsen, David; Platt, Michael; Huettel, Scott A.; Brannon, Elizabeth M. (Frontiers in Psychology, 2011)
Adolescents often make risky and impulsive decisions. Such behavior has led to the common assumption that a dysfunction in risk-related decision-making peaks during this age. Differences in how risk has been defined across studies, however, make it difficult to draw conclusions about developmental changes in risky decision-making. Here, we developed a non-symbolic economic decision-making task that can be used across a wide age span and that uses coefficient of variation (CV) in reward as an index of risk. We found that young children showed the strongest preference for risky compared to sure bet options of equal expected value, adolescents were intermediate in their risk preference, and young adults showed the strongest risk aversion. Furthermore, children's preference for the risky option increased for larger CVs, while adolescents and young adults showed the opposite pattern, favoring the sure bet more often as CV increased. Finally, when faced with two gambles in a risk–return tradeoff, all three age groups exhibited a greater preference for the option with the lower risk and return as the disparity in risk between the two options increased. These findings demonstrate clear age-related differences in economic risk preferences that vary with choice set and risk. Importantly, adolescence appears to represent an intermediate decision-making phenotype along the transition from childhood to adulthood, rather than an age of heightened preference for economic risk.